Optimisation of raw jack fruit fries and its physicochemical and sensory properties - Ray, Babu R M; T, Bala Narasaiah; Suresh, Challa (Journal of Postharvest Technology, 2024)
The jack fruit is a god’s gift to humankind due to its many uses. It takes care of human, animal food and nutritional needs effortlessly. Apart from several value-added products from ripe fruits, the unripe raw fruits can be converted into ready to eat foods of longer shelf life. In the present study, matured raw jackfruit pulp and moisture equilibrated starch was cooked and dried at different ratios viz., T1(100:100), T2(100:50), T3(100:30), T4(50:100), T5(30:100), T6(10:100), T7(100:20), T8(20:100), T9(100:10) with 100 % jack-pulp as control TC (0:100). The dried products called raw fries were deep-fried and air-puffed. The blend 50:100 (T4) based fries were best rated with an oil uptake of 28.62g/100 at 194℃ ±4 ℃for 10.32sec frying time temperature with complete moisture loss produced 174% thick and 65.35% dia expanded product that took an average peak break force (PBF) of 0.18 kg, compared to 138% thick and 28.72% dia expanded product of 6.23% moisture content in air-puffing time-temperature of 24.66 sec, 198±2℃ demanded 0.57 kg PBF. The blend 30:100 (T5) reported 25.43g/100g oil uptake in 10.40 sec, yielding 120.07% thick, 45.90% dia product demanding 0.14kg braking force, against its counterpart air-fried product in 22.00 sec puffing time produced 153% thick, 29 % dia product of 6.84% per cent moisture, demanding 0.27 kg maximum force to break. The colour difference ΔE is positive (1.94), which is higher in T6(16.30), T7(13.90) and Tc(13.59) due to varying levels of starch and pulp. Hence 30% -50% starch is rated as the best blend. The dried raw fries were safe for consumption beyond eight months of storage.